Implementasi Pembangunan Zona Integritas Untuk Mewujudkan Wilayah Bebas Korupsi Di SMK Negeri 8 Medan Melalui Permen PAN RB Nomor 90 Tahun 2021 - Siregar, Salsabila Balqis; Nababan, Ramsul (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study analyzes the implementation of the Integrity Zone (ZI) development at SMK Negeri 8 Medan as an effort to realize a Corruption-Free Zone (WBK) based on the Regulation of the Minister of Administrative and Bureaucratic Reform Number 90 of 2021. A descriptive qualitative approach was used with in-depth interviews, observation, and documentation techniques with 15 informants consisting of the principal, vice principal, teachers, education staff, and students. Data were analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results show that the implementation of ZI at SMK Negeri 8 Medan is running with partial effectiveness. Positive aspects include the elimination of extortion practices, improved quality of administrative services, and strengthened leadership commitment. However, there are significant gaps such as the lack of a dedicated ZI team, sporadic implementation of the six areas of change, and limitations in the monitoring and evaluation system. The level of understanding of the ZI concept among the school community shows an asymmetry between high behavioral commitment and low conceptual understanding. The main obstacles include the absence of an institutional framework, limited resources, and coordination failures. This study concludes that although there has been progress in increasing transparency and accountability, the implementation of ZI requires strengthening institutional capacity and comprehensive training programs to achieve WBK status sustainably.